2020
DOI: 10.1007/s42452-020-2214-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of drilling responses using GRA on Al-6063/TiC composite

Abstract: The aim of the current work is to optimize the drilling constraints simultaneously during drilling of an Al6063/TiC composite based on grey relational analysis. Drilling trials were performed on Al-6063 reinforced with 15 wt% titanium carbide (TiC) of size 50 μm. HSS twist drills with diameter of 10 mm under lubricated condition were utilized for performing drilling tests. Drilling parameters explicitly helix angle, spindle speed, feed rate and responses such as surface roughness, cutting force and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…GRA is a way of transforming two or more responses into a single response. In the sub-sections, the method for measuring the GRA is explained (Reddy et al , 2020a, b, c, d; Kumar et al , 2020). Step 1: Normalization…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GRA is a way of transforming two or more responses into a single response. In the sub-sections, the method for measuring the GRA is explained (Reddy et al , 2020a, b, c, d; Kumar et al , 2020). Step 1: Normalization…”
Section: Resultsmentioning
confidence: 99%
“…The top two effectible process parameters on the responses are utilized for developing the contour plots (Reddy et al , 2020a, b, c, d). The contour plots can be helpful for simultaneous observation of two factors on the responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TOPSIS was developed by Hwang and Yoon in 1985, and it is used to find the ideal solution and the non-ideal solution by using the normalized matrix and then calculate the relative distance from the ideal solution [16,17]. GRA was proposed by Deng in 1982, and it is used to predict, make decisions and solve various uncertain problems [18][19][20]. Sina et al [21] found that TOPSIS method could be used to select the parameter combination and obtain better cutting effect in the abrasive water jet cutting process.…”
Section: Introductionmentioning
confidence: 99%